ETHICS AND MANAGEMENT OF INFORMATION IN NEUROGENETIC STUDIES IN CUBA - MARTÍN HERNÁNDEZ, I.; PITA RODRÍGUEZ, M.; ZALDÍVAR VAILLANT, T. (MEDECINE LEGALE DROIT MEDICAL, 2025)
The biotechnological and medical genetics development in Cuba has given rise to the possibility of accessing the precise genetic information about its population. Consequently, the collection, storage, processing, handling and disclosure of genetic data must be subject to appropriate security measures and respect for pronounced ethical standards and regulations, for their protection. The present work describes the experience of researchers from a Department of Neurogenetics in the management of genetic information, as well as mentions some of the ethical dilemmas that they face in their daily work.